PENGARUH RETURN ON ASSET, EARNING PER SHARE, DEBT TO EQUITY RATIO, UKURAN PERUSAHAAN, DAN ARUS KAS AKTIVITAS OPERASI TERHADAP RETURN SAHAM (Studi Empiris Terhadap Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2017) - Cahayani Nurrul; indrawati Novita; L Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this study is to find out the Return On Assets, Earning PerShare, Debt to Equity Ratio, Firm Size and Operating Activity Cash Flow onStock Returns. The population in this study are manufacturing companies listedon the Indonesia Stock Exchange 2015-2017. Sampling by using a purposivesampling method, so that the research sample was 58 companies with a period of3 years, so that the number of data obtained 174. In this study using 5 variables,namely the dependent variable is stock returns, while the independent variablesare return on assets, earnings per share, debt to equity ratio, firm size, andoperating activity cash flow. Analysis of the data used is multiple linearregression. The results showed: 1) Return On Assets (ROA) affect stock returns,2) Earning Per Share (EPS) does not affect stock returns, 3) Debt to Equity Ratio(DER) does not affect stock returns, 4) Firm size affect stock returns, and 3)Operating activity cash flow has an effect on stock returns.Keywords: Return On Assets, Earning Per Share, Debt to Equity Ratio, Firm Size,Operating Activity Cash Flow, Stock Return